2020
DOI: 10.1108/ijbm-09-2019-0332
|View full text |Cite
|
Sign up to set email alerts
|

The role of the media in socially responsible investing

Abstract: PurposeThis study aims to understand how media content and media sentiment in corporate social responsibility (CSR) news coverage affect investment performance, as reflected in the S&P 500 Environmental and Socially Responsible Index from 2010 to 2016.Design/methodology/approachComputer-assisted content analysis and sentiment analysis are employed to analyze 818 CSR-related newspaper articles from mainstream newspapers. Autoregressive model is used to comprehend socially responsible investment (SRI) perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
(89 reference statements)
0
6
0
Order By: Relevance
“…While we are unable to definitively determine the specific personal reason(s) behind SRI, this study allowed us to contribute to the emerging literature on individual motives of SRI (find a recent review of emerging themes in Daugaard 2020) and expand on three possibilities. First, this study provides additional evidence of how CSR-related news influence investors' attitudes about the evaluation of the stock market and their investment decisions afterwards, which appears positively associated with SRI (Lei and Zhang 2020;W. Yang et al 2017).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…While we are unable to definitively determine the specific personal reason(s) behind SRI, this study allowed us to contribute to the emerging literature on individual motives of SRI (find a recent review of emerging themes in Daugaard 2020) and expand on three possibilities. First, this study provides additional evidence of how CSR-related news influence investors' attitudes about the evaluation of the stock market and their investment decisions afterwards, which appears positively associated with SRI (Lei and Zhang 2020;W. Yang et al 2017).…”
Section: Discussionmentioning
confidence: 72%
“…Second, investors in such difficult times filled with financial market uncertainty are particularly inclined to favour those companies using news coverage and media content to communicate their CSR actions. Since the study of media coverage remains an emerging topic in the SRI literature (e.g., Lei and Zhang 2020), media coverage of CSR actions was considered to reflect on the collective beliefs about COVID-19. As Bourghelle (2005) noted, financial investors usually all read the same press and listen to the same experts, so the media is an essential mediator in the formation of collective beliefs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In his seminal work on the construction of media reputation as a corporate strategic resource, Deephouse (2000) has shown the positive relationship between the amount (or favorableness) of media reputation and the bank's return on assets and how a bank's media favorableness is a valuable, difficult-to-imitate, non-substitutable resource which banks in a single market compete to build. By analyzing historical data on corporate social responsibility (CSR) media coverage and socially responsible index (SRI), Lei and Zhang (2019) have shown the impact of media content and media sentiment of CSR-related news articles on SRI. Vogler et al (2016) showed how the infomediation of powerful stakeholders can impact the reputation of a company.…”
Section: Literature Reviewmentioning
confidence: 99%